Desenvolvimento e avaliação do protótipo de uma semeadora puncionadora para agricultura familiar - Melo, Rafaela Paula (2017)
Family-based agriculture is responsible for most food consumed in Brazil, thus it takes an important part in the country's agricultural production. However, family-based farmers deal with peculiarities regard to the technology levels adopted by the production system since most of the family-based farms still make use of agricultural equipment of low technology levels. Therefore, the inclusion of technologies that contribute with the boost of labor quality in family-based agriculture is necessary. In that way, researches are being conducted for designing seeders able to perform sowing process in equidistant holes that allow reliable and precise distribution since seeders equipped with punch system cause less soil to revolve and provide a direct contact with the soil. This work aimed to design, build and evaluate the performance of punch seeder prototype for family-based agriculture. The test took place at the experimental field of Department of Agricultural Engineering of Federal University of Ceará. The soil was classified as Yellow-Red Clay Soil. Field trials were conducted in order to verify the prototype's performance. Satisfactory results were obtained regarding seeds and fertilizer's distribution. Basic descriptive statistic was used to evaluate the following parameters: mean, standard deviation, coefficient of variance, coefficients of symmetry and kurtosis. The Statistical Process Control (SPC) was meant to evaluate the quality process control of seed and fertilizer distribution. Failure Mode and Effect Analysis (FMEA) was employed in order to propose modifications needed for project's improvement. The prototype presented an optimum index of seed distribution, as it obtained 90.2% acceptable spacing and the fertilizing process met the specifications according to its adjustment Quality study conducted by SPC indicated the adequacy of sowing process with quality standards. The project's critical failures were listed through the FMEA and solutions were obtained according to the severity of their effects, allowing prototype's improvement.